2014
DOI: 10.1021/jp505902m
|View full text |Cite
|
Sign up to set email alerts
|

Disordered Structural Ensembles of Vasopressin and Oxytocin and Their Mutants

Abstract: Vasopressin and oxytocin are intrinsically disordered cyclic nonapeptides belonging to a family of neurohypophysial hormones. Although unique in their functions, these peptides differ only by two residues and both feature a tocin ring formed by the disulfide bridge between first and sixth cysteine residues. This sequence and structural similarity are experimentally linked to oxytocin agonism at vasopressin receptors and vasopressin antagonism at oxytocin receptors. Yet single-or double-residue mutations in bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
47
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(55 citation statements)
references
References 54 publications
8
47
0
Order By: Relevance
“…Regarding protein disorder levels, these receptors follow a similar trend as observed for the ligand OXT and AVP nonapeptides, which have been described as intrinsically disordered (Yedvabny et al , 2015). The suggestion that the level of disorder is maintained throughout evolution to promote a wide range of interaction among proteins and other molecules has been subject of intense debate (Schlessinger et al.…”
Section: Discussionsupporting
confidence: 57%
“…Regarding protein disorder levels, these receptors follow a similar trend as observed for the ligand OXT and AVP nonapeptides, which have been described as intrinsically disordered (Yedvabny et al , 2015). The suggestion that the level of disorder is maintained throughout evolution to promote a wide range of interaction among proteins and other molecules has been subject of intense debate (Schlessinger et al.…”
Section: Discussionsupporting
confidence: 57%
“…The TIP4P-Ew water model reproduces a number of experimental measurements for disordered cyclic peptides, vasopressin and oxytocin (43), and amyloid-β proteins (38,44). The new TIP4P-D model has increased water dispersion interactions and better approximates global conformational properties of intrinsically disordered proteins (IDPs) (36,45) and FG repeats in particular (35), enabling more accurate simulation of protein dynamics.…”
Section: Resultsmentioning
confidence: 97%
“…A variety of simulation methods (MD, Monte Carlo, metadynamics, replica exchange) and different levels of representation (coarse-grained, implicit solvent, all-atom with explicit water) have been used to obtain IDP ensembles. 7,[21][22][23][24][25][26][27][28][29] There are two main challenges encountered in de novo simulations.…”
Section: Introductionmentioning
confidence: 99%
“…On the one hand, good agreement between computed and measured experimental observables was observed in some IDP simulations. [23][24][25]27,28,42,[44][45][46] On the other hand, the accuracy of unfolded state and IDP structural ensembles obtained using several widely-used force fields has been called into question. [25][26][27]43,[46][47][48][49][50][51][52][53] Piana et al suggested that modern force fields, including Amber ff99sb*-ildn and CHARMM 22* in particular, produce IDP and unfolded state ensembles that are on average too compact.…”
Section: Introductionmentioning
confidence: 99%